diff --git a/Common/Real/Sequence.tex b/Common/Real/Sequence.tex index 06f4fa1..beb681c 100644 --- a/Common/Real/Sequence.tex +++ b/Common/Real/Sequence.tex @@ -13,32 +13,125 @@ \section{Summations}% \label{sec:summations} -\subsection{\unverified{Arithmetic Series}}% +\subsection{\verified{Arithmetic Series}}% \label{sub:sum-arithmetic-series} Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$. Then for some $n \in \mathbb{N}$, - $$\sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}.$$ + \begin{equation} + \label{sub:sum-arithmetic-series-eq1} + \sum_{i=0}^n a_i = \frac{(n + 1)(a_0 + a_n)}{2}. + \end{equation} \begin{proof} \lean{Common/Real/Sequence/Arithmetic} {Real.Arithmetic.sum\_recursive\_closed} + \divider + + Let $(a_i)_{i \geq 0}$ be an arithmetic sequence with common difference $d$. + By definition, for all $k \in \mathbb{N}$, + \begin{equation} + \label{sub:sum-arithmetic-series-eq2} + a_k = (a_0 + kd). + \end{equation} + Define predicate $P(n)$ as "identity \eqref{sub:sum-arithmetic-series-eq1} + holds for value $n$." + We use induction to prove $P(n)$ holds for all $n \geq 0$. + + \paragraph{Base Case}% + + Let $k = 0$. + Then $$\sum_{i=0}^k a_i = a_0 = \frac{2a_0}{2} = + \frac{(k + 1)(a_0 + a_k)}{2}.$$ + Therefore $P(0)$ holds. + + \paragraph{Induction Step}% + + Assume induction hypothesis $P(k)$ holds for some $k \geq 0$. + Then + \begin{align*} + \sum_{i=0}^{k+1} a_i + & = \sum_{i=0}^k a_i + a_{k+1} \\ + & = \frac{(k + 1)(a_0 + a_k)}{2} + a_{k+1} + & \text{induction hypothesis} \\ + & = \frac{(k + 1)(a_0 + (a_0 + kd))}{2} + (a_0 + (k + 1)d) + & \eqref{sub:sum-arithmetic-series-eq2} \\ + & = \frac{(k + 1)(2a_0 + kd)}{2} + (a_0 + (k + 1)d) \\ + & = \frac{(k + 1)(2a_0 + kd) + 2a_0 + 2(k + 1)d}{2} \\ + & = \frac{2ka_0 + k^2d + 4a_0 + kd + 2kd + 2d}{2} \\ + & = \frac{(k + 2)(2a_0 + kd + d)}{2} \\ + & = \frac{(k + 2)(a_0 + a_0 + (k + 1)d)}{2} \\ + & = \frac{(k + 2)(a_0 + a_{k+1})}{2} + & \eqref{sub:sum-arithmetic-series-eq2} \\ + & = \frac{((k + 1) + 1)(a_0 + a_{k+1})}{2}. + \end{align*} + Thus $P(k)$ implies $P(k + 1)$ holds true. + + \paragraph{Conclusion}% + + By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true. + \end{proof} -\subsection{\unverified{Geometric Series}}% +\subsection{\verified{Geometric Series}}% \label{sub:sum-geometric-series} Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$. Then for some $n \in \mathbb{N}$, - $$\sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}.$$ + \begin{equation} + \label{sub:sum-geometric-series-eq1} + \sum_{i=0}^n a_i = \frac{a_0(1 - r^{n+1})}{1 - r}. + \end{equation} \begin{proof} \lean{Common/Real/Sequence/Geometric} {Real.Geometric.sum\_recursive\_closed} + \divider + + Let $(a_i)_{i \geq 0}$ be a geometric sequence with common ratio $r \neq 1$. + By definition, for all $k \in \mathbb{N}$, + \begin{equation} + \label{sub:sum-geometric-series-eq2} + a_k = a_0r^k. + \end{equation} + Define predicate $P(n)$ as "identity \eqref{sub:sum-geometric-series-eq1} + holds for value $n$." + We use induction to prove $P(n)$ holds for all $n \geq 0$. + + \paragraph{Base Case}% + + Let $k = 0$. + Then $$\sum_{i=0}^k a_i = a_0 = \frac{a_0(1 - r)}{1 - r} = + \frac{a_0(1 - r^{k+1})}{1 - r}$$ + Therefore $P(0)$ holds. + + \paragraph{Induction Step}% + + Assume induction hypothesis $P(k)$ holds for some $k \geq 0$. + Then + \begin{align*} + \sum_{i=0}^{k+1} a_i + & = \sum_{i=0}^k a_i + a_{k+1} \\ + & = \frac{a_0(1 - r^{k+1})}{1 - r} + a_{k + 1} + & \text{induction hypothesis} \\ + & = \frac{a_0(1 - r^{k+1})}{1 - r} + a_0r^{k + 1} + & \eqref{sub:sum-geometric-series-eq2} \\ + & = \frac{a_0(1 - r^{k+1}) + a_0r^{k+1}(1 - r)}{1 - r} \\ + & = \frac{a_0(1 - r^{k+1} + r^{k+1}(1 - r))}{1 - r} \\ + & = \frac{a_0(1 - r^{k+1} + r^{k+1} - r^{k+2})}{1 - r} \\ + & = \frac{a_0(1 - r^{k+2})}{1 - r} \\ + & = \frac{a_0(1 - r^{(k + 1) + 1})}{1 - r}. + \end{align*} + Thus $P(k)$ implies $P(k + 1)$ holds true. + + \paragraph{Conclusion}% + + By mathematical induction, it follows for all $n \geq 0$, $P(n)$ is true. + \end{proof} \end{document}